(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
This article presents the results of a study on the absorption capacity and the composition of absorbed bases in light gray gypsiferous soils with stony-gravelly structure subjected to varying degrees of erosion. The research was conducted on light gray soils formed in the Polvontosh foothills of the Southern Fergana region and in the Pop district of Namangan region. The article provides data on the total absorbed bases of the soils and the quantities of exchangeable cations (Ca²⁺, Mg²⁺, K⁺, Na⁺) in the absorbing complex.